Fur Processing in Raižiai in the 20th Century: Craft and Image - Mardosa, Jonas (Lietuvos istorijos studijos, 2023)
In Lithuania, fur processing craft used to change depending on the social, cultural and even political context of the development of the state and the nation. In the Tatar community of Raižiai several craftsmen were engaged in fur processing. The artisans were in direct contact with the fur craftsmen working in Butrimonys and the surrounding villages. In this way, the fur processing craft habitat was formed, the centre of which was Raižiai. The article examines the fur processing craft in Raižiai and its surroundings on the basis of archival data and ethnological literature. The forms of fur processing craft transfer between gene rations and their change over time are examined. The aim of the article is to reveal the essence of the Tatar famous business in Raižiai in the context of the history of Lithuanian crafts and to highlight the specific features of the life of the local Tatar community. The main period of existence of the fur processing craft in Raižiai was before the Soviet era. The analysis of ethnographic field research data showed that the longstanding vertical folk direction for the transmission of the secrets of the craft ensured the viability of the fur processing tradition in the Tatar families. Therefore, the article considers the emergence and existence of the image of the Tatars as fur processing craftsmen as a phenomenon of a unique business. Fur processing was part of the Tatar business, but the craft nurtured throughout its long history, has naturally shaped the image of the Tatars as exceptional masters in the field. The need for furs for peasant clothing due to climatic conditions of Lithuania helped to achieve such mastery, therefore, people were looking for wellperforming craftsmen. The professionalism of the craftsmen, the use of tra ditional methods of fur processing, supported the profound appreciation of the level of mastery of the Tatars in the society. Even the changes in the handicraft of preSoviet Lithuania and the desire of the state to expand the layer of crafts men which increased the internal competition of craftsmen, did not reduce the authority of the Tatar fur processing craftsmen. Therefore, in the perspective of the technological changes in the fur processing of the 20th century, the Tatars of Raižiai were cautious about innovation. Such attitude was appreciated by the customers and the quality of the work ensured the demand for the craft. After World War II, the situation had changed. First of all, private business was forbid den, therefore, fur craftsmen had to work illegally; they received bans from the authorities, and even fines were imposed. The surviving fur processing craftsmen in the Soviet era, like the majority of the rural population, were used for unskilled labour in the collective farms and on a Soviet farm. The analysis of the collect ed material indicates that the Soviet era which began to destroy the craft due to ideological circumstances, and the change in the direction of the activity needs of In Lithuania, fur processing craft used to change depending on the social, cultural and even political context of the development of the state and the nation. In the Tatar community of Raižiai several craftsmen were engaged in fur processing. The artisans were in direct contact with the fur craftsmen working in Butrimonys and the surrounding villages. In this way, the fur processing craft habitat was formed, the centre of which was Raižiai. The article examines the fur processing craft in Raižiai and its surroundings on the basis of archival data and ethnological literature. The forms of fur processing craft transfer between gene rations and their change over time are examined. The aim of the article is to reveal the essence of the Tatarfamous business in Raižiai in the context of the history of Lithuanian crafts and to highlight the specific features of the life of the local Tatar community. The main period of existence of the fur processing craft in Raižiai was before the Soviet era. The analysis of ethnographic field research data showed that the longstanding vertical folk direction for the transmission of the secrets of the craft ensured the viability of the fur processing tradition in the Tatar families. Therefore, the article considers the emergence and existence of the image of the Tatars as fur processing craftsmen as a phenomenon of a unique business. Fur processing was part of the Tatar business, but the craft nurtured throughout its long history, has naturally shaped the image of the Tatars as exceptional masters in the field. The need for furs for peasant clothing due to climatic conditions of Lithuania helped to achieve such mastery, therefore, people were looking for wellperforming craftsmen. The professionalism of the craftsmen, the use of tra ditional methods of fur processing, supported the profound appreciation of the level of mastery of the Tatars in the society. Even the changes in the handicraft of preSoviet Lithuania and the desire of the state to expand the layer of crafts men which increased the internal competition of craftsmen, did not reduce the authority of the Tatar fur processing craftsmen. Therefore, in the perspective of the technological changes in the fur processing of the 20th century, the Tatars of Raižiai were cautious about innovation. Such attitude was appreciated by the customers and the quality of the work ensured the demand for the craft. After World War II, the situation had changed. First of all, private business was forbid den, therefore, fur craftsmen had to work illegally; they received bans from the authorities, and even fines were imposed. The surviving fur processing craftsmen in the Soviet era, like the majority of the rural population, were used for unskilled labour in the collective farms and on a Soviet farm. The analysis of the collect ed material indicates that the Soviet era which began to destroy the craft due to ideological circumstances, and the change in the direction of the activity needs of a modernizing society, destroyed the way of life of the society, therefore, the craft of Raižiai Tatars, having a hundredyear history, naturally disappeared at the end of the 20th century.